Error-correction coding and decoding : bounds, codes, decoders, analysis and applications /: bounds, codes, decoders, analysis and applications. ([2017]) - Tomlinson, Martin; Tjhai, Cen Jung; Ambroze, Marcel A; Ahmed, Mohammed; Jibril, Mubarak
No abstract available